Feline Differential Leukocyte Count with ProCyte Dx: Frequency and Severity of a Neutrophil‐Lymphocyte Error and How to Avoid It - Tvedten, H.W. (J Vet Intern Med, 2017)
BACKGROUND: Erroneous neutrophil and lymphocyte counts from analysis of feline blood samples were transferred directly into the hospital information system from the ProCyte Dx hematology instrument in our after‐hours laboratory. Errors usually were not detected by the users. HYPOTHESIS/OBJECTIVES: To quantify the frequency and severity of errors associated with the ProCyte Dx analyzer and to identify methods to avoid the errors. ANIMALS: One‐hundred six EDTA blood samples routinely submitted from feline hospital patients were analyzed. METHODS: ProCyte differential leukocyte counts were compared to 2 reference methods: Advia 2120 hematology instrument and manual enumeration. Limits for unacceptable deviation from the reference methods were defined as 18 for % lymphocytes and 23 for % neutrophils. RESULTS: Fourteen of 106 samples had unacceptable errors for both lymphocytes and neutrophils compared to both reference methods. Median % lymphocytes in those 14 samples were 11.2, 15.0, and 53.0% for Advia, manual, and ProCyte, respectively. Median % neutrophils were 85.4, 81.5, and 34.2% for Advia, manual, and ProCyte, respectively. All errors were avoided by rejecting automated ProCyte differential leukocyte results whenever the dot plot appeared clearly incorrect, but only 9 of these 14 samples had a ProCyte WBC distribution error flag. CONCLUSIONS AND CLINICAL IMPORTANCE: Results reported by ProCyte had markedly falsely increased lymphocyte and decreased neutrophil counts in 13% of feline patient samples. Users must reject automated differential leukocyte count results when the WBC dot plot appears overtly incorrect. Rejection based only on ProCyte WBC error flag was insufficient.